If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4h + 6 = 32 Reorder the terms: 6 + 4h = 32 Solving 6 + 4h = 32 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 4h = 32 + -6 Combine like terms: 6 + -6 = 0 0 + 4h = 32 + -6 4h = 32 + -6 Combine like terms: 32 + -6 = 26 4h = 26 Divide each side by '4'. h = 6.5 Simplifying h = 6.5
| (11x-9)-(4x+6)= | | 50=-7+-3 | | 2h=124+8h-362 | | y=9.4x+12.5 | | 5(x-4)=3(3x+4) | | a=1/2x7-4 | | 24x^5y^3+88x^3y^2-40x^2y=0 | | 1/3(3x-9)=2x-3 | | 19=7+2n | | 13g=117 | | 3(r+4)-r=2(r+a) | | 5x/4=6 | | coskt(49k^2-64)=0 | | Sin(x)=.41 | | 7z=12 | | y=4k^2-25 | | 16=-12/5a | | 5+10s=10s | | 2x+30=2x-2 | | y=49k^2-64 | | .5x+.5y=12 | | 0.18+0.1(20-a)=0.14(20) | | 14q=4 | | 7(x+8)+x=4(x+5)+4 | | a(x+a)=1 | | 2x+9=77 | | 1-7r=-7r | | 4x+4=10x-10 | | 21-9=21 | | -1.7x=2(x+2.18) | | 7x-6y+5z=26 | | 2*cos(x)=x |